Psychology of Communication : course of lectures. Lecture 3. Topic: Presentation skills Topic: Critical thinking. Topic 5 - Луценко, Олена Львівна; Lutsenko, O. L. (Харків : Харківський національний університет імені В.Н. Каразіна, 2020)
Topic 5. Presentation and self-presentation skills: Basic definitions. Impression management. Visual, verbal and nonverbal means. Nervous control. Rehearsals.
Keywords: communication; psychology; medical; healh care